Chapter Haitians live for news - Exumé, David (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
In Brooklyn, radio programs conducted by and for Haitian immigrants have been historically vital tools for those seeking information to survive both under an ideologically restrictive dictatorship and as newcomers in an unfamiliar country. These radio stations and their blend of news and culture programming served as sonic reminders of community, connecting them not just to current events in the United States, but also to news from their country of origin. Through interviews with staff members at three different kinds of radio stations-college-owned, subcarrier, and pirate-this essay explores the role of Haitian radio in community-building, activism, and citizenship for Haitians who arrived in the U.S. in the 1980s. These programs, which existed on the periphery of a competitive media market, embodied a virtual community for Haitians that superseded nation-state boundaries.